Physicochemical Studies of Catalytic Converters Found in Some Used Cars - Aburawi, Moammar Bashir; Alhalib, Abdullah Abdulsalam; Al-mabrook, Selima Ali Mohammed (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
In this research, the mechanism of operation of the catalytic converter found in cars was studied, and a catalytic converter was chosen for a Korean-made car, a 2008 Hyundai Sonata model, used for a distance of 230,000 km. Also, 2 grams were taken from a used original catalytic converter and another commercial one for the same car, and an analysis was conducted using (ICP) (Inductively Coupled Plasma) device and it was The percentages of results for the original sample are better than the results for the commercial sample because the commercial sample had greater percentages of materials that make up the ceramic material than the original sample, which makes the original sample efficient and has good chemical and physical properties.
Keywords: Catalytic converter; Catalysis; Catalytic metals